2019
DOI: 10.12688/f1000research.20645.1
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Acute hemorrhagic edema of infancy (Seidlmayer purpura) – a dramatic presentation for a benign disease

Abstract: We present a case of an 11-month-old girl who was referred to our unit for an erythematous rash that appeared on the face and extremities. Personal and family history was not relevant. Laboratory tests were normal. During recovery, diameter and colour intensity of the cutaneous lesions increased, but after some weeks, lesions had a self-limited resolution without any treatment. Based on clinical and laboratory findings, a diagnosis of acute hemorrhagic edema of infancy (AHEI) was made. AHEI is a rare cutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The Köbner sign occurred in a total of 32 cases, comprised of 21 males and 11 females 11 [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] months of age. A total of 42 Köbner signs ( Table 2 ) were documented in the mentioned 32 cases [ 14 , 21 , 23 , 24 , 27 , 31 , 37 , 40 , 43 , 45 , 47 , 49 , 50 , 54 , 59 , 60 , 61 , 63 , 65 , 66 , 67 , 69 , 72 , 78 , 79 , 80 , 81 , 83 , 84 , 85 , 86 , 89 ]. Lower legs, thighs, waistline, and groins were the most affected regions.…”
Section: Resultsmentioning
confidence: 99%
“…The Köbner sign occurred in a total of 32 cases, comprised of 21 males and 11 females 11 [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] months of age. A total of 42 Köbner signs ( Table 2 ) were documented in the mentioned 32 cases [ 14 , 21 , 23 , 24 , 27 , 31 , 37 , 40 , 43 , 45 , 47 , 49 , 50 , 54 , 59 , 60 , 61 , 63 , 65 , 66 , 67 , 69 , 72 , 78 , 79 , 80 , 81 , 83 , 84 , 85 , 86 , 89 ]. Lower legs, thighs, waistline, and groins were the most affected regions.…”
Section: Resultsmentioning
confidence: 99%
“…19 Despite the rapid progression of lesions, AHEI is a self-limited disease with spontaneous and complete resolution, often occurring within 1-3 weeks. 20 Affected patients rarely have recurrent attacks and complications, like scarring lesions as well as renal, gastrointestinal, or joint involvement. AHEI has no specific treatment, and conservative management is the most common approach.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic factors have been investigated due to family-based investigations, but genetic studies revealed no role for HLA-B27, HLA-Cw6 or HLA-DR, PSTPIP2, LPIN2 and NOD2. 1,2 Variants rs10889677, rs2201841, rs7517847 of IL-23R and rs2243248 of IL-4 showed strong associations with SAPHO syndrome. 3 Our results for rs7517847 of IL-23R and rs2243248 of IL-4 were similar to Guo's results.…”
Section: The Role Of Genetic Factors and Peripheral Immune Cells In Sapho Syndromementioning
confidence: 92%
“…AHE, also known as Seidlmayer purpura, is a rare and benign leukocytoclastic vasculitis, typically described in young children and usually triggered by infections, drugs or vaccination. 1 The main clinical characteristics are symmetrically purpuric medallion-or cockade-shaped patches, associated with painful oedema and predominantly located on cephalic extremity or limbs. Although cutaneous presentation may be dramatic, in children, disease remains non-toxic, visceral involvement is rare and the disease is self-remitting within a few days.…”
mentioning
confidence: 99%